From Knowledge to Action, Analysis of the Decision Making Process in Africa : the Case of the State Contract Teacher Policy - (:unkn) unknown (My University, 2011)
Policy analysis in Africa has mainly focused on their evaluation. Now that several reforms are undertaken and that the progressive move toward democracy allows new actors to enter the political arena, it is useful to analyze how decisions on public issues are made. The dissertation examines the reform of the teacher recruitment policy in francophone Africa. The reform consisted in changing the teacher status in order to allow the government to pay a lower salary to new teachers. The drawbacks of the usual policy and research from the area of economics of education demonstrating that the reform was necessary put the issue on the agenda. If many countries adopted it, some have not. Factors that triggered the reforms vary among countries: the severity of the lack of teachers, the existence of a high number of teachers paid by the communities, and mainly pressure from donors through external aid. In some countries, the civil society was more involved in the policy process. However, this involvement did not block the reform; neither did it prevent the reform from diverting significantly from the usual policy.
Keywords: African Research